Fumaric Acid in Broiler Nutrition: A Dose Titration Study and Safety Aspects - Islam, K.M.S.; Schuhmacher, A.; Aupperle, H.; Gropp, J.M. (International Journal of Poultry Science, 2008)
Six isonitrogenous (22.8% CP) and isocaloric diets (13 MJ ME/kg) containing 0, 1.25, 2.50, 3.75, 5.0 and 7.5% fumaric acid (FA), respectively, were fed for 26 days to 12 (replicates) x 8 (chicks per replicate) Lohmann-Hybrid newly hatched male chicks (48 g body weight) per treatment. The diets consisted mainly of wheat and soybean meal. Mortality ranged between 0 and 4 %. Final body weight (and feed efficiency) amounted to 1,506 (756), 1,597 (767), 1,532 (754), 1,485 (759), 1,342 (738) and 1,378 g (747 g gain/kg feed) for the groups with 0, 1.25, 2.50, 3.75, 5.0 and 7.5% FA, respectively. The 1.25% FA group showed significantly (p<0.05) better weight gain than all other groups and better feed efficiency than the groups with 5.0 and 7.5% FA. Higher gain was associated with higher feed intake. Body weight of the 5.0 and 7.5% FA groups was significantly lower than that of all other groups. It is concluded that 1.25% FA may promote growth of broilers, but the effect disappears with further increasing doses. The relative weight of heart, liver and spleen was not affected by the treatment. Pathological findings summarized to 5/10 in the 7.5% FA group, to 1/10 in the control and to 2-3/10 in the other groups. The 7.5% FA group showed also the highest incidence of kidney alterations and slightly thinner duodenal wall. From the findings the margin of safety is concluded to be about 3% (3.75/1.25) considering 1.25% FA in the broiler diet as the optimally effective concentration.